Clinical evaluation of low-shrinkage bioactive material giomer versus nanohybrid resin composite restorations: A two-year prospective controlled clinical trial - Toz Akalın, Tuğba; Öztürk Bozkurt, Funda; Kuşdemir, Mahmut; Özsoy, Alev; Yüzbaşıoğlu, Emir; Özcan, Mutlu (NLM (Medline), 2023)
This study evaluated the clinical performance of low-shrinkage bioactive resin composite compared with a conventional nanohybrid resin composite. A total of 35 patients (18 males, 17 females; mean age: 29±9 years old) received, randomly, 35 pairs of fillings restored with either low-shrinkage bioactive material employing Giomer filler technology (Beautifil II LS, Shofu Inc, Kyoto, Japan) or conventional nanohybrid resin composite (Clearfil Majesty Posterior, Kuraray, Japan) in Class I and Class II cavities. Two operators made all the restorations using the corresponding adhesive resins: FL-Bond II (Shofu Inc) and Clearfil SE Bond (Kuraray), according to each manufacturer's instructions. Two calibrated operators evaluated the restorations two weeks after placement (baseline), at six months, and at one and two years using FDI criteria (Scores 1-5). Data were analyzed using the McNemar test (?=0.05). Mean observation time was 27.4 ± 4.1 months (min=20.8; max=33.7). In both groups, according to FDI criteria, the restorations were mostly rated with best scores (Score 1 or 2) for biological, functional, and optical parameters. For one filling in the group restored with nanohybrid resin composite, a small and localized secondary caries lesion was observed and monitored at the one- and two-year follow-ups. One restoration in the low-shrinkage Giomer restorative group was accepted as a failure due to retention loss. Over the two-year follow-up, both the Giomer and the nanohybrid resin composite restorations' performance was clinically acceptable.
Keywords: Bioactive Material; Resin Composite Restorations; Giomer Versus Nanohybrid